1985
DOI: 10.1056/nejm198510173131602
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking, Serum Estrogens, and Bone Loss during Hormone-Replacement Therapy Early after Menopause

Abstract: To elucidate the effect of smoking on estrogen metabolism, we examined 136 postmenopausal women treated for one year with one of three different doses of combined estrogen-progestogen or placebo. The women were grouped according to smoking status, and serum levels of estrone and estradiol were measured before and after treatment. The results showed reduced levels of both estrogens in smokers as compared with nonsmokers in all three dosage groups. This reduction was most pronounced in the high-dose group (4 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
108
2
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(117 citation statements)
references
References 12 publications
6
108
2
1
Order By: Relevance
“…However, coitrary to what might be expected, parity and (early) age at menarche were not (positively) related to bone mass. Smoking may enhance both the metabolic inactivation of oestrogens (Jensen et al, 1985) and early menopause (Lesko et al, 1985), and therefore could have a negative influence on BMD. the present study is significantly reduced in osteoporotic women compared to controls (Riggs et al, 1981;Kr0lner & Nielsen, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…However, coitrary to what might be expected, parity and (early) age at menarche were not (positively) related to bone mass. Smoking may enhance both the metabolic inactivation of oestrogens (Jensen et al, 1985) and early menopause (Lesko et al, 1985), and therefore could have a negative influence on BMD. the present study is significantly reduced in osteoporotic women compared to controls (Riggs et al, 1981;Kr0lner & Nielsen, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, factors associated with reduced circulating oestrogen levels may consequently reduce the risk of this malignancy (Baron, 1984;Baron et al, 1990). In this regard, it has been hypothesised that smoking might be inversely related to levels of circulating oestrogen (Jensen et al, 1985;Baron et al, 1990;Weiderpass and Baron, 2001). Supporting this hypothesis are studies that have shown that smoking is associated with increased risk of osteoporosis (Jensen et al, 1985;Jensen and Christiansen, 1988) and may attenuate the reduction in serum total and low-density lipoprotein cholesterol associated with exogenous hormone use (HRT) (Jensen and Christiansen, 1988).…”
Section: Epidemiologymentioning
confidence: 99%
“…Jensen et al (1985) found that smoking reduced the serum concentrations of El and E2 in postmenopausal women taking ERT: they could not detect any effect of smoking on endogenous El or E2 concentrations, but these concentrations were at the lower limit of sensitivity of their assay. They concluded that smoking increases metabolic clearance of E2.…”
mentioning
confidence: 92%